2017
DOI: 10.4315/0362-028x.jfp-17-083
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Aflatoxin M1 in Breast Milk and Its Association with Nutritional and Socioeconomic Status of Lactating Mothers in Lebanon

Abstract: Aflatoxin B (AFB) is the most potent of the dietary aflatoxins, and its major metabolite, aflatoxin M (AFM), is frequently found in the breast milk of lactating mothers. The aim of this study was to assess the occurrence and factors associated with AFM contamination of breast milk collected from lactating mothers in Lebanon. A total of 111 breast milk samples were collected according to the guidelines set by the World Health Organization. Samples were analyzed with a competitive enzyme-linked immunosorbent ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…The determined incidence rate was comparably higher than in HBM studies performed in Brazil [ 22 ], Iran [ 21 , 29 ], and Turkey [ 30 ]. The average and maximum levels were comparable with studies previously conducted in Cyprus [ 31 ] and Lebanon [ 32 ]. However, the maximum level determined among the Portuguese population was nearly 10 times below the maximum levels registered in studies conducted in Jordan [ 33 ] and Egypt [ 34 ].…”
Section: Mycotoxinssupporting
confidence: 88%
“…The determined incidence rate was comparably higher than in HBM studies performed in Brazil [ 22 ], Iran [ 21 , 29 ], and Turkey [ 30 ]. The average and maximum levels were comparable with studies previously conducted in Cyprus [ 31 ] and Lebanon [ 32 ]. However, the maximum level determined among the Portuguese population was nearly 10 times below the maximum levels registered in studies conducted in Jordan [ 33 ] and Egypt [ 34 ].…”
Section: Mycotoxinssupporting
confidence: 88%
“…8,9 Indeed, AFB1 metabolite known as aflatoxin M1 (AFM1) is frequently found in milk, samples of cord blood, and colostrum in pregnant women, which signify the possibility of prenatal contact to AFB1 in humans. 1012 Aflatoxins were reportedly detected in semen samples (40%) obtained from infertility clinics amid a higher chance of sperm anomaly compared with fecund men living within a locality in Nigeria. 13 Moreover, data from experimental animals have demonstrated that AFB1 may be an essential risk factor for male infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggested that the epidemiology of aflatoxin contamination of the food system is liable seasonal and agroecological variations (Elaridi et al., 2017; Kılıç Altun et al., 2017). Aflatoxin contamination tends frequently to occur in warm and humid settings (Wild, 2017), and various seasonal patterns have also been reported (Elaridi et al., 2017; Kılıç Altun et al., 2017). Accordingly, we analyzed the AFB1 contamination of family foods and urinary excretion of AFM 1 among lactating women in Sidama, southern Ethiopia, and compared the levels across different agroecological settings (lowland, midland, and highland) and seasons (wet and dry).…”
Section: Introductionmentioning
confidence: 99%